Revitalizing cultural heritage: Strategies for teaching Indonesian traditional music in elementary schools - Sularso, Sularso; Jazuli, Muhammad; Djatiprambudi, Djuli; Hanshi, Bao (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
This study focuses on the integration of Indonesian traditional music education at the elementary school level as a strategy for promoting culture in Indonesia. It recognizes the significance of social capital, cultural capital, and knowledge capital as the foundation for fostering a comprehensive and systematic approach to cultural development. The research employs interview, observation, and literature review methods to gather data, guided by three key questions: (1) the current state of traditional music teaching in Indonesian elementary schools, (2) the strategies employed in integrating traditional music education, and (3) the outcomes of the Archipelago Traditional Music pre-congress in 2021 within the paradigm of elementary school music education. The analysis is primarily based on the implementation of previous policies and programs, particularly those managed by the Ministry of Education and Culture. The study's findings reveal several important aspects, including: (1) the need for statutory regulations supporting the conservation of traditional music programs, (2) fostering active collaboration between teachers and traditional artists or musicians through open participation, (3) providing necessary facilities and infrastructure to create an ecosystem conducive to traditional music education at the elementary school level, (4) implementing training programs to enhance the traditional music competence of elementary school teachers, and (5) involving the traditional music community in the design of the curriculum for traditional music education in elementary schools. These results underscore the importance of integrating traditional music education at the elementary school level to promote Indonesian culture. By implementing the suggested strategies, policymakers and educators can contribute to the preservation and development of traditional music, creating a stronger cultural foundation within Indonesian society.